2022
DOI: 10.3390/ijms23062912
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Melatonin and Misoprostol against Experimentally Induced Increases in Intestinal Permeability in Rats

Abstract: Intestinal mucosal barrier dysfunction caused by disease and/or chemotherapy lacks an effective treatment, which highlights a strong medical need. Our group has previously demonstrated the potential of melatonin and misoprostol to treat increases in intestinal mucosal permeability induced by 15-min luminal exposure to a surfactant, sodium dodecyl sulfate (SDS). However, it is not known which luminal melatonin and misoprostol concentrations are effective, and whether they are effective for a longer SDS exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Several studies have suggested that melatonin plays a significant role in alleviating ER‐stress across various models and conditions 74,75 . Interestingly, melatonin has been indicated to protect against surfactant‐induced, 76,77 and ethanol‐induced 78,79 increases in small intestinal mucosal permeability in rats, highlighting its potential as a treatment for a compromised intestinal mucosal barrier. While this protective effect has been shown to be primarily receptor‐mediated, 77 it could also be attributed to its pleiotropic effects on ER‐stress signaling pathways 74,75,80 .…”
Section: Therapeutic Strategies Targeting Er‐stress In Mucositismentioning
confidence: 99%
“…Several studies have suggested that melatonin plays a significant role in alleviating ER‐stress across various models and conditions 74,75 . Interestingly, melatonin has been indicated to protect against surfactant‐induced, 76,77 and ethanol‐induced 78,79 increases in small intestinal mucosal permeability in rats, highlighting its potential as a treatment for a compromised intestinal mucosal barrier. While this protective effect has been shown to be primarily receptor‐mediated, 77 it could also be attributed to its pleiotropic effects on ER‐stress signaling pathways 74,75,80 .…”
Section: Therapeutic Strategies Targeting Er‐stress In Mucositismentioning
confidence: 99%
“…The intestinal mucosa barrier plays a crucial role in preventing noxious contents of the intestinal lumen, in order to maintain systemic homeostasis [ 1 ]. The disruption of the epithelial barrier will increase intestinal permeability, leading to leaky gut syndrome [ 2 ].…”
Section: Introductionmentioning
confidence: 99%